ANXIETY, DEPRESSION AND PERCEIVED SOCIAL SUPPORT AMONG COVID-19 PATIENTS ADMITTED TO A COVID CARE CENTRE IN UTTARAKHAND, INDIA - Mohd Najmul Aqib Khan; Mohd Maroof; Preeti; Rupali Gupta; Azmi Naaz; Sadhana Awasthi (The Indonesian Journal of Public Health, 2025)
Introduction: The mental health of individuals infected with the COVID-19 pandemic was impacted. There was an increased surge into panic and stresses; in the first year of the COVID-19 epidemic, anxiety and depression-like mental diseases surged 25% globally. Aims:  This study assessed the levels of anxiety, depression, and perceived social support among individuals diagnosed with COVID-19, their predicting factors, and documented the correlation between these. Methods: This cross-sectional study included 346 asymptomatic to mildly ill COVID-19 patients. Hospital anxiety and depression scale assessed depression and anxiety, while MSPSS assessed perceived social support. SPSS version 16 was used for data analysis. Tests used included ANOVA, Pearson's rank correlation test, independent t-tests, and multivariate linear regression. A p-value below 0.05 was deemed statistically significant. Results: A total of 13.8 percent patients had comorbid depression and 32 percent, anxiety. 35.2 percent patients did not have enough support. A significant correlation between depression and anxiety, and a relationship of depression and anxiety with social support, was noted. The regression analysis revealed; substantial association between anxiety and depression with age, marital status, covid case in family, and hypertension: an association of diabetes mellitus was seen with anxiety only; and perceived social support was found to have a significant association with age, covid case in family, and presence of diabetes mellitus and hypertension. Conclusion: Significant number of COVID-19 experienced anxiety, depression, and a lack of social support.